2020
DOI: 10.5530/pj.2020.12.146
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Nephroprotective Activity of Artemisia absinthium L. on Diclofenac-induced Toxicity in Rats

Abstract: Background: Artemisia absinthium L. is known for its antimalarial activity however, hepatoprotective activity of aqueous extracts has also been reported but, nephroprotective activity not yet evaluated. Objective: To evaluate the hepatoprotective and nephroprotective activities of A. absinthium against diclofenac-induced toxicity on rats. Materials and Methods: Three different doses of methanol and ethyl acetate extract of A. absinthium (50, 100 and 200 mg/kg/day) were evaluated and compared with silymarin 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…29 It has been reported that treatment of ibuprofen and celecoxib, NSAID drugs, in rats at a dose of 40 mg/kg for 28 days increased liver and kidney function parameters. 30 Like these drugs, the treatment of DF in rats at a dose of 10 mg/kg intramuscularly for 14 days 31 and 50 mg/kg intraperitoneally for 2 days 32 has been reported to increase AST, ALT and ALP activity levels as well as BUN and creatinine levels. Similarly, this study found that DF increased liver enzyme activities and kidney function parameters, whereas TA treatment reduced these values.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has been reported that treatment of ibuprofen and celecoxib, NSAID drugs, in rats at a dose of 40 mg/kg for 28 days increased liver and kidney function parameters. 30 Like these drugs, the treatment of DF in rats at a dose of 10 mg/kg intramuscularly for 14 days 31 and 50 mg/kg intraperitoneally for 2 days 32 has been reported to increase AST, ALT and ALP activity levels as well as BUN and creatinine levels. Similarly, this study found that DF increased liver enzyme activities and kidney function parameters, whereas TA treatment reduced these values.…”
Section: Discussionmentioning
confidence: 99%
“…The blood specimens collected from the jugular vein were analyzed for different biochemical parameters and the dissected livers were evaluated by histopathologic techniques. 32…”
Section: Methodsmentioning
confidence: 99%
“…The blood specimens collected from the jugular vein were analyzed for different biochemical parameters and the dissected livers were evaluated by histopathologic techniques. 32 Macroscopic Viewing of the Liver. The dissected liver organs were cleaned with normal saline (cold), and dried by the filter papers for the estimation of gross weight and gross morphological studies.…”
Section: Hepatoprotective Trialmentioning
confidence: 99%
“…The treatment period was 7 days before induction and 3 days after. The doses of A. vulgaris extracts and the duration of treatment were selected according to previous studies (29)(30)(31). The body weight of the rats was measured at the beginning and end of the interventions using an FEW (Japan) scale with a sensitivity of 1 g.…”
Section: Experimental Groupsmentioning
confidence: 99%